The capacity and potentials of Budapest to attract creative economy - Egedy, Tamás; Kovács, Zoltán (Hungarian Geographical Bulletin, 2009)
The triggering factors of urban development have changed continuously over the past decades, always adapting themselves to the processes of globalisation and to the related trends. As a consequence of the shift from the Fordist production system to the post-Fordist economic structures the metropolitan regions have acquired an ever growing importance and became the centres of economic and social development of countries and regions. International experience shows that in economic competition an increasing role is played by creativity (and particularly by culture), invention and innovation. Concerning further development of the European metropolitan regions it might be decisive how these cityregions will be able to attract and integrate firms in the sphere of the creative knowledge sector and their manpower. Regarding to the new economic development tendencies drawn above this paper highlights the capacity and potentials of the Budapest Metropolitan Region based on statistical analyses and results of empirical questionnaire surveys and in-depth interviews carried out amongst employees, managers and transnational migrants working in the creative knowledge sector